The Association Between Marital Status, Coronary Computed Tomography Imaging Biomarkers, and Mortality in a Lung Cancer Screening Population. Issue 3 (May 2020) - Celeng, Csilla; Takx, Richard A.P.; Lessmann, Nikolas; Maurovich-Horvat, Pál; Leiner, Tim; Išgum, Ivana; de Jong, Pim A.
Abstract : Purpose: The purpose of this study was to elucidate the impact of being unmarried on coronary computed tomography (CT) imaging biomarkers and mortality in a lung cancer screening population. Materials and Methods: In this retrospective case-control study, 5707 subjects (3777 married; mean age: 61.9±5.1 y and 1930 unmarried; mean age: 61.9±5.3 y) underwent low-dose CT as part of the National Lung Screening Trial (NLST). The median follow-up time was 6.5 (Q1-Q3: 5.6 to 6.9) years. Being unmarried was defined as never married, widowed, separated, or divorced. Being married was defined as married or living as married. Our primary endpoint was cardiovascular disease (CVD)-related death; our secondary endpoint was all-cause mortality. Coronary CT imaging biomarkers (calcium score, density, and volume) on low-dose chest CT scan were calculated using dedicated automatic software. Weighted Cox proportional-hazards regression was performed to examine the association between marital status and death. Kaplan-Meier curves were generated to visualize subject survival. Results: Being unmarried was significantly associated with an increased risk for CVD-related death (hazard ratio [HR]: 1.58; 95% confidence interval [CI]: 1.31-1.91) and all-cause mortality (HR: 1.39; 95% CI: 1.26-1.53), which remained significant even after adjusting for traditional cardiovascular risk factors (HR CVD death: 1.75; 1.44-2.12 and HR all-cause mortality: 1.58; 95% CI: 1.43-1.74) and coronary calcium score (HR CVD death: 1.58; 95% CI: 1.31-1.91 and HR all-cause mortality: 1.40; 95% CI: 1.27-1.54). Conclusions: Being unmarried is associated with an increased CVD-related death and all-cause mortality mainly due to cardiovascular etiology. On the basis of this, marital status might be taken into consideration when assessing individuals' health status.